The concept of variable and the 3UV model: A literature review - Castro-Fernández, Felipe; Lop-Herrera, Reinier; Juárez-López, José Antonio (Journal of Didactic Mathematics, 2024)
Based on a literature review covering the time period 2005-2023, the objective of this article is to present the research trends on the concept of variable and the contributions for its study made through the theoretical framework called Model of the Three Uses of the Variable (Model 3UV). For this reason, a documentary research design was developed with a qualitative approach and at a descriptive level. The instruments for the collection and analysis of information were a search log, a bibliographic matrix, and a synthesis matrix, elaborated in the Excel software. The technique used to carry out the documentary review was the content analysis, from the deductive analytical categories: objective, research method and conclusion. The advanced search was carried out in Academic Google and of the total results obtained, the 10 most relevant articles published during the period 2005-2023 were selected. One of the main findings found was the identification of three trends in research with Model 3UV: the first, related to teaching proposals; the second, concerning the understanding of difficulties in the learning of students; and the third, concerning teaching materials.